2023
DOI: 10.3390/microorganisms12010020
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium with Eight Tandem Copies of blaNDM-1 on a HI2 Plasmid

Huijuan Song,
Siyu Zou,
Yi Huang
et al.

Abstract: Carbapenem-resistant Salmonella has recently aroused increasing attention. In this study, a total of four sequence type 36 Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) isolates were consecutively isolated from an 11-month-old female patient with a gastrointestinal infection, of which one was sensitive to carbapenems and three were resistant to carbapenems. Via antibiotic susceptibility testing, a carbapenemases screening test, plasmid conjugation experiments, Illumina short-reads, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Another study focusing on egg farm environments in Western Australia reported a high incidence of Salmonella [14]. While antibiotic resistance can occur naturally, the emergence of most resistant organisms is attributed to the acquisition of resistance genes through mutations or the transfer of genetic material, followed by selective pressure [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Another study focusing on egg farm environments in Western Australia reported a high incidence of Salmonella [14]. While antibiotic resistance can occur naturally, the emergence of most resistant organisms is attributed to the acquisition of resistance genes through mutations or the transfer of genetic material, followed by selective pressure [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%